CORPORATE OWNERSHIP, KARAKTERISTIK EKSEKUTIF, DAN INTENSITAS ASET TETAP TERHADAP PENGHINDARAN PAJAK - Umi Sulistiyanti; R. Andro Zylio Nugraha (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2019)
Tax avoidance is a legal action carried out by corporate taxpayer to reduce, minimize, and alleviate the tax burden in the manner permitted by law. Nowdays, there are a lot of tax avoidance cases in Indonesia. Indonesia is ranked 11th largest with the highest tax avoidance cases with an estimated value of 6.48 billion US dollars. This study aims to analyze the Influence of corporate ownership, executive characteristics, and the intensity of fixed assets on tax avoidance.The research’s population of this study were 152 manufacturing companies listed in Indonesia Stock Exchange (IDX) in 2015,2016, and 2017. This research samples were 62 companies or 167 observation data selected by purposive sampling method. The data used secondary data that obtained from Indonesia Stock Exchange (IDX) and it was analyzed by multiple regression.The results of the study show that Family Ownership and Institutional Ownership have no effect on Tax Avoidance. While managerial ownership has a positive effect on Tax Avoidance. Executive characteristics and Intensity of Fixed Assets have negative effect on Tax Avoidance.